2019
DOI: 10.3390/ijms20081966
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Berberine on Broiler P-glycoprotein Expression and Function: In Situ and In Vitro Studies

Abstract: Overcoming P-glycoprotein (P-gp) efflux is a strategy to improve the absorption and pharmacokinetics of its substrate drugs. Berberine inhibits P-gp and thereby increases the bioavailability of the P-gp substrate digoxin in rodents. However, the effects of berberine on P-gp in chickens are still unclear. Here, we studied the role of berberine in modulating broilers P-gp expression and function through both in situ and in vitro models. In addition, molecular docking was applied to analyze the interactions of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Moreover, P-gp is an important member of the ATP-binding transport family, which can pump exogenous substances out of the cell with the energy generated by the hydrolysis of ATP, thereby reducing the concentration of the drug in the cell ( Peachey et al., 2017 ). Various components in fruits and vegetables and traditional Chinese medicines in daily life can regulate the activity of P-gp, and could thereby affect the intestinal absorption of P-gp substrates ( Bhutto et al., 2018 ; Zhang et al., 2019 ). It has been reported that quercetin and rutin significantly reduce the oral bioavailability of cyclosporine through activating P-gp ( Yu et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, P-gp is an important member of the ATP-binding transport family, which can pump exogenous substances out of the cell with the energy generated by the hydrolysis of ATP, thereby reducing the concentration of the drug in the cell ( Peachey et al., 2017 ). Various components in fruits and vegetables and traditional Chinese medicines in daily life can regulate the activity of P-gp, and could thereby affect the intestinal absorption of P-gp substrates ( Bhutto et al., 2018 ; Zhang et al., 2019 ). It has been reported that quercetin and rutin significantly reduce the oral bioavailability of cyclosporine through activating P-gp ( Yu et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 46 ] revealed that enrofloxacin, tilmicosin, ciprofloxacin, and ampicillin are the co-substrate of P-gp and BCRP (Breast cancer resistance protein). The Papp of enrofloxacin, tilmicosin, ciprofloxacin, and ampicillin to the MDCK-chAbcb1 cell models was obviously enhanced by co-incubation with berberine (P-gp inhibitor) [ 47 ]. Combining duodenum-targeted release with non-pharmacological activity inhibitor agents will be a potential method to improve the oral absorption of these VAs.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, eggshell thickness and strength rapidly returned to normal, indicating that verapamil is metabolized in a short time. Early studies focused on the effects of verapamil on chicken biventer-cervicis muscle [ 35 ], atherosclerotic chickens [ 36 , 37 ], and shifts in drug–drug interactions when broilers were treated with the specific P-glycoprotein inhibitor verapamil [ 38 ]. It is uncommon to add verapamil to the chicken’s diet during egg production, and few studies have focused on the effects of verapamil on layers and chicken egg quality although verapamil could attenuate lipopolysaccharide [ 39 ] and colibacillosis [ 30 ] in broilers when treated with oral enrofloxacin.…”
Section: Discussionmentioning
confidence: 99%